Photonics modeling and design - Sujecki, Sawomir (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Photonics Modeling and Design delivers a concise introduction to the modeling and design of photonic devices. Assuming a general knowledge of photonics and the operating principles of fibre and semiconductor lasers, this book:Describes the analysis of the light propagation in dielectric mediaDiscusses heat diffusion and carrier transport Applies the presented theory to develop fibre and semiconductor laser models Addresses the propagation of short optical pulses in optical fibres Puts all modeling into practical context with examples of devices currently in development or on the market Providing hands-on guidance in the form of MATLAB scripts, tips, and other downloadable content, Photonics Modeling and Design is written for students and professionals interested in modeling photonic devices either for gaining a deeper understanding of the operation or to optimize the design'--
Chapter 1. Introduction -- chapter 2. Light propagation in homogenous media -- chapter 3. Optical waveguides -- chapter 4. Beam propagation method -- chapter 5. Thermal modelling of photonic devices -- chapter 6. Flow of current in semiconductor photonic devices -- chapter 7. Fibre amplifiers and lasers -- chapter 8. Laser diode modelling -- chapter 9. Pulse propagation in optical fibres.
Includes bibliographical references and index.
Keywords: Optoelectronic devices -- Mathematical models; Optoelectronic devices -- Design and construction; Photonics